2010
DOI: 10.1093/nar/gkq1239
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the small regulatory RNA MicA by ribonuclease III: a target-dependent pathway

Abstract: MicA is a trans-encoded small non-coding RNA, which downregulates porin-expression in stationary-phase. In this work, we focus on the role of endoribonucleases III and E on Salmonella typhimurium sRNA MicA regulation. RNase III is shown to regulate MicA in a target-coupled way, while RNase E is responsible for the control of free MicA levels in the cell. We purified both Salmonella enzymes and demonstrated that in vitro RNase III is only active over MicA when in complex with its targets (whether ompA or lamB m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 60 publications
3
61
0
Order By: Relevance
“…The low levels of MicA found in hfq mutants strongly decrease the probability of base-pairing with target mRNAs. The down-regulation in sRNA-target mRNA duplexes probably explains the impairment in RNase III activity on MicA, in agreement with in vitro studies (Viegas et al 2011). Data suggest that the degradation of small RNAs that are not associated with Hfq mainly occurs in a targetindependent pathway, in which RNase III has a reduced impact.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The low levels of MicA found in hfq mutants strongly decrease the probability of base-pairing with target mRNAs. The down-regulation in sRNA-target mRNA duplexes probably explains the impairment in RNase III activity on MicA, in agreement with in vitro studies (Viegas et al 2011). Data suggest that the degradation of small RNAs that are not associated with Hfq mainly occurs in a targetindependent pathway, in which RNase III has a reduced impact.…”
Section: Discussionsupporting
confidence: 84%
“…In vitro studies showed that Salmonella RNase III can cleave MicA when bound to its target ompA mRNA (Viegas et al 2011). To further analyze the role of RNase III in cells without Hfq, we constructed and analyzed double mutants lacking both Hfq and RNase III.…”
Section: Inactivation Of Pnpase Markedly Increases the Levels Of Smalmentioning
confidence: 99%
“…For construction of the pWSK29hfq plasmid (pSVA-6) expressing hfq, a PCR fragment containing the entire hfq sequence was amplified from the SL1344 chromosome, digested with the enzymes HindIII and XbaI, and ligated into plasmid pWSK29 digested with the same enzymes. For the construction of plasmid pWSK29rnc (pSVA-7), the pSVDA-01 plasmid expressing His-tagged RNase III (20) was digested with BamHI and XbaI to obtain the rnc fragment, which was ligated with pWSK29 digested with the same enzymes. In the case of plasmid pSVA-8 expressing RNase E, a PCR fragment containing the entire rne sequence was amplified from SL1344 chromosome and was cloned into the XbaI and EcoRI sites of the pSE420 vector (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…Several genome-wide analyses reported that the absence of RNases E and III in E. coli (14) and RNase III in Bacillus subtilis (15) or Staphylococcus aureus (16,17) affects the abundance of a high number of mRNAs and sRNAs. Namely, in Salmonella and in other bacteria, RNases E and III have roles in the control of a number of sRNAs implicated in the regulation of outer membrane proteins (18)(19)(20) and important virulence factors (11,21,22).…”
mentioning
confidence: 99%
“…In addition to these diverse single-strand-specific RNases, most bacteria also encode the double-strand-specific RNase III (10). This enzyme is highly conserved in bacteria and eukaryotes and has a critical role in posttranscriptional regulation, where it cleaves double-stranded substrates, such as those resulting from the base pairing of an mRNA and noncoding RNA (11), or those associated with highly structured RNAs, such as ribosomal RNAs (rRNAs) (12,13). There can be considerable functional interplay between RNases, with a classic example being the generation of mature 23S, 16S, and 5S rRNAs from a single 30S transcript.…”
mentioning
confidence: 99%